ЗАСАГЛАЛЫН МЕХАНИЗМ, ТҮҮНИЙ МӨН ЧАНАР - Ц.Батболд (Politology, 2023)
In the article clarification incornate policy by conceptyal politicians in the market, provocation mechanism of power in adoption, not a little beneficial largest framework reform doing in the political system. In action government meaningful and essentiality of mechanism instigate and prohibit, descriptive by to set a good/bad example and model and scheme.